Farmersâ Perception to The Role of Extension Workers on Kaligesing Goat Farm Management in Kaligesing, Purworejo - Guntoro, Budi; Wahyudi, Wahyudi; Sulastri, Endang (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. The aims of this research were to describe the characteristics of Kaligesing goat farmers; to analyze the farmersâ perceptions on the role of extension workers as conduit of information, as mentors, organizers and dynamic factor, technicians and liaisons; to discover the relationship between the farmersâ characteristics with farmersâ perceptions; and to investigate the relationship between farmersâ perceptions to goat maintenance management. The respondents were goat farmers in Kaligesing, Purworejo, Central Java Province. Data were obtained from questionnaire survey method. Determining location, the research applied combination of stratified sampling method with purposive random sampling. Total respondents were 159 farmers with nine farmer groups as samples. Analysis was subject to Spearman Rank, resulting that age, education level and farming experience were not significant to the farmersâ perceptions to the role of extension workers, but the ownership of livestock had a very significant relationship with a correlation coefficient of 0.240, group classes had also very significant relationship with a correlation coefficient of 0.414, and frequency of meeting with extension workers have a significant relationships with a correlation coefficient of 0.202. Farmersâ perceptions to the role of extension workers had very significant relationships to the maintenance management with a correlation coefficient of 0.393.Â Key words : farmersâ characteristics, farmersâ perceptions, Kaligesing goat, role of extension workersÂ Abstrak. Penelitian ini bertujuan untuk mengetahui karakteristik peternak, persepsi peternak terhadap peran penyuluh, hubungan antara karakteristik peternak dengan persepsi, dan hubungan antara persepsi peternak dengan manajemen pemeliharaan. Responden penelitian adalah peternak Kambing Kaligesing di Kecamatan Kaligesing Kabupaten Purworejo Jawa Tengah dengan metode penelitian survei kuesioner. Penentuan lokasi penelitian dengan kombinasi cara stratified sampling dan purposive random sampling. Jumlah kelompok tani sebagai sampel penelitian sebanyak sembilan kelompok dan jumlah total responden sebanyak 159 peternak. Analisis Rank Spearman digunakan untuk analisis data. Â Hasil analisis menunjukkan Â bahwa umur, tingkat pendidikan dan lama beternak tidak secara nyata memiliki hubungan dengan persepsi peternak terhadap peran penyuluh, sedangkan kepemilikan ternak memiliki hubungan sangat nyata (P<0,01) dengan nilai koefisien korelasi 0,240. Kelas kelompok memiliki hubungan sangat nyata (P<0,01) dengan nilai koefisien korelasi 0,414 dan frekuensi bertemu penyuluh memiliki hubungan nyata (P<0,05) dengan nilai koefisien korelasi 0,202. Persepsi peternak terhadap peran penyuluh memiliki hubungan sangat nyata (P<0,01) terhadap manajemen pemeliharaan dengan nilai koefisien korelasi 0,393Kata kunci:Â karakteristik peternak, persepsi peternak, kambing Kaligesing, peran penyuluh